Penerapan Assessmen Kinerja Berbasis Model Cooperative Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik - Himsar Himsar; Muhammad Taufik Sibagariang (Institut Agama Islam Negeri Padangsidimpuan, 2022)
The learning process through instant social media through Google fosters a selfish attitude towards students, learning without the process of finding problems, making hypotheses and solving problems. The performance of students becomes weak towards the completion of learning and the eroded cohesiveness of each student. The implementation of cooperative learning model-based performance assessment is one of the efforts to regenerate students' attitudes that are damaged and their learning declines. This research uses PTK (Classroom Action Research) which consists of 2 cycles. Before conducting the research, an initial test was conducted with an attitude class average of 65, knowledge 63.5 and skills 60.5, meaning that it was still below the KKM (Minimum Completeness Criteria) of 70. Researchers conducted learning using cooperative learning models in cycles I and II. The average value of the first cycle class is attitude 75.6, knowledge 80.4 and skills 78.6, meaning that every aspect of the student's value is above the KKM 70. In the second cycle, the students got better scores than the pre-research and the first cycle, namely the average attitude class score was 85.8, the knowledge value was 85.6 and the skill score was 85.8, meaning the average grade value was above the KKM. The results of this study can improve the declining learning process and grow student performance processes, cooperative attitudes, eliminate selfish attitudes and improve students' critical thinking skills.